LAW AND CIVILIZATION: NORBERT LIAS AS A REGULATION THEORIST - Jusmadi, Jusmadi; Haironi, Haironi; Masyduki, Masyduki; Jusnaidi, Jusnaidi; Helman, Mhd; Misran, Misran; Cuadmadja, Anera Irinsyahinta; Fikri, KMS. Novyar Satriawan (Yayasan Education and Social Center, 2025)
German sociologist Norbert Elias devised a comprehensive sociological analysis of the interconnections between the processes of state formation, institutional dynamics, individual subjectivity, habitus, and the logic of their transformation over time. The historical sociology of the self, violence, crime and punishment, organizations, emotions, sexuality, social control, and sports are just a few of the many areas in which his work has significantly influenced social scientific thinking. His views have only sometimes been applied to other areas of law and social science study, with his influence in legal academia centered on criminology. This review emphasizes the potential future directions in which Elias's process-figurational approach could advance in sociolegal research and scholarship by outlining (a) the core elements of Elias's